Mucosal injuries from indwelling catheters: A scoping review. - Katarina E Göransson; Ann-Christin von Vogelsang; Gabriella Engström (PLoS ONE)
There is currently a lack of clarity concerning the types and frequency of mucosa injuries occurring in urine bladders among patients with indwelling urine catheters that are of modern design and material. The aim of the study was to identify and present the available information regarding mucosa injuries in urine bladders among adult patients with indwelling urine catheters. The research question was: What is known about mucosa injuries in urine bladders among patients with indwelling urine catheters? A scoping review applying the patient, exposure, and outcome framework. A preliminary search was made to identify the keywords, and the selection process followed the Preferred Reporting Items for Systematic Review and Meta-Analysis flow diagram. The final search across five databases retrieved a total of 8,883 records. Eight studies from three countries were included and the studies used two main methods for collecting data. Eleven concepts to describe the injuries were identified, with a range from one to five studies using the same concept. Mucosa injuries, of which polypoid cystitis was most frequently reported, occurred in all studies, and ranged from 41% to 100% per study. The size of injured area varied between 0.5 to 2.5 cm. The posterior wall of the bladder was the most common area where injuries were found. This scoping review sheds light on the limited understanding of mucosal injuries in urine bladders among adult patients with indwelling urinary catheters. Moving forward, concerted efforts are warranted to bridge existing knowledge gaps to enhance our understanding of mucosal injuries and improve clinical outcomes for adult patients with indwelling urinary catheters. The lack of a robust scientific base for the impact of indwelling urine catheters on the urine bladder mucosa warrants future studies.